(untitled) (American Journal of Economics and Business Innovation, 2025)
This study examines the link between spend rewards and vouchers and how they influence consumer behavior. Spend rewards and vouchers are strong drivers that initiate purchasing behavior, alter the spending habits of consumers, and build reward-based consumer loyalty. This study aims to determine the link between spend rewards and vouchers and examines how these promotional tools affect the purchasing behavior of consumers in e-commerce and online shopping. The quantitative design uses a questionnaire to collect data from internet consumers. The questionnaire collects data on consumers’ spending, the consumers’ attitudes towards vouchers and rewards, and usage frequency of the incentives. Random sampling was used to select participants for the study. Statistical analysis involves determining the percentage distribution of the responses to identify patterns and relationships. The findings indicate a high positive relationship between spend rewards and voucher availability and higher consumer spending. A large proportion of the respondents state that these rewards have an impact on their purchasing behavior, resulting in greater participation and repeat business. These findings imply that providing spend rewards and vouchers is a sound approach to increasing customer retention and driving sales. In conclusion, the research verifies that spend rewards and vouchers has a positive effect on consumer behavior by making purchases more frequent and building brand loyalty. The findings give confidence that the adoption of such incentive schemes can yield positive results for companies in the e-commerce sector.